A clinical staging model of psychotic disorders based on a long-term follow-up of first-admission psychosis: A validation study. (April 2023) - Peralta, Victor; de Jalón, Elena García; Moreno-Izco, Lucía; Peralta, David; Janda, Lucía; Sánchez-Torres, Ana M.; Cuesta, Manuel J.; ,; Ballesteros, A.; Fañanás, L.; Gil-Berrozpe, G.; Hernández, R; et al.
Highlights: We developed a novel clinical staging model of psychosis based on the long-term course and outcome of 243 first-episode psychosis followed-up for a mean of 21 years. The model's validity was assessed by means of 22 baseline predictors, 23 construct-related variables and 31 outcome variables. The model showed good inter-rater reliability and sound construct, outcome and predictive validity. Eight baseline variables independently accounted for 49.9% of the variance of staging. Abstract: We examined the empirical validity of a staging model of psychotic disorders primarily based on their long-term course. The model distinguished 6 consecutive stages (2A, 2B, 3A, 3B, 4A, 4B) based on symptom recurrence, persistence and progression, such as functional decline. We analyzed data from 243 participants with first-admission psychosis who were followed-up for a mean of 20.9 years and assessed for 22 baseline variables, 23 construct-related variables and 31 outcome variables. Later stages scored significantly poorer than early stages on most validators by showing generally medium to large effect sizes and a dose-response pattern, thus confirming the validity of the model. For each set of validators, differences between consecutive stages were especially evident for stages 2 and 3A, although many variables from each validation realm also differentiated between the consecutive stages 3A and above. Baseline predictors including familial load of schizophrenia, neurodevelopmental impairment, childhood adversity, treatment delay, negative symptoms, neurological impairment and poor early response to treatment, independently accounted for 49.9% of the variance of staging. A staging model of psychosis based primarily on its long-term course has sound construct, outcome and predictive validity, which may inform about stage indicators and predictors of clinical stages from psychosis onset.